Rancang Bangun Aplikasi Penjualan Berbasis Web pada UMKM HJM Garage Jonggol, Jawa Barat - Mulyana, Dadang Iskandar; Nuradi, Fahmi; Sofia, Agiah; Saputri, Rosalina; Kolbia, Ummi (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
The web-based sales application designed and developed for UMKM HJM Garage in Jonggol, West Java, aims to provide the much-needed support of information technology in their business operations. UMKM HJM Garage faces several challenges, including the lack of systematic reporting, difficulty in maintaining inventory availability, and struggles in tracking expenses and profits regularly. The objective of this application is to assist UMKM HJM Garage in enhancing productivity and simplifying its sales processes. It is equipped with inventory management, order tracking, and sales reporting features, expected to facilitate effective business management. With the implementation of this web-based sales application, it is anticipated that UMKM HJM Garage will manage sales more efficiently and significantly increase their revenue.